2021
DOI: 10.1186/s12891-021-04179-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects on pain, physical function, and quality of life of quadriceps strengthening exercises combined with Baduanjin qigong in older adults with knee osteoarthritis: a quasi-experimental study

Abstract: Background Exercise is recommended as a principal treatment for individuals with knee osteoarthritis (KOA). However, the best choice for an optimal exercise program able to promote long-term compliance in KOA patients is not clear. This study aims to compare the effect of combined exercise (CE: quadriceps strengthening exercises (QSE) and Baduanjin qigong training (BDJ)) versus QSE alone and BDJ alone on older adults with KOA. Methods A three-arm, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…Almost all studies included both women and men, except (Cheung et al, 2017 ) which did not report sex ratios and (Qiu, 2018 ) which included only women. A total of 11 studies (64.7%) (Raub, 2002 ; Cheung et al, 2014 , 2017 ; Wang et al, 2016 , 2021 ; Hu, 2017 ; Song et al, 2017 ; Cao, 2018 ; Qiu, 2018 ; Ye et al, 2019 ; Xiao et al, 2020 ) included patients who suffer chronic pain from KOA. Three studies (Teut et al, 2016 ; Cao, 2018 ; Liu et al, 2019 ) included patients with CLBP and three studies (Yang et al, 2005 ; von Trott et al, 2009 ; You et al, 2018 ) included other chronic pain patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost all studies included both women and men, except (Cheung et al, 2017 ) which did not report sex ratios and (Qiu, 2018 ) which included only women. A total of 11 studies (64.7%) (Raub, 2002 ; Cheung et al, 2014 , 2017 ; Wang et al, 2016 , 2021 ; Hu, 2017 ; Song et al, 2017 ; Cao, 2018 ; Qiu, 2018 ; Ye et al, 2019 ; Xiao et al, 2020 ) included patients who suffer chronic pain from KOA. Three studies (Teut et al, 2016 ; Cao, 2018 ; Liu et al, 2019 ) included patients with CLBP and three studies (Yang et al, 2005 ; von Trott et al, 2009 ; You et al, 2018 ) included other chronic pain patients.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers implemented various mindful exercise interventions, which included yoga [two Hatha yoga (Cheung et al, 2014 , 2017 ) and one Viniyoga (Teut et al, 2016 )], TC [two Yang-style TC (Wang et al, 2016 ; Song et al, 2017 ); one Chen-style TC (Liu et al, 2019 ); one Sun-style TC (Raub, 2002 ); and three just demonstrated TC (Hu, 2017 ; Cao, 2018 ; You et al, 2018 )], and qigong [five Baduanjin qigong (Ding, 2014 ; Hu, 2017 ; Qiu, 2018 ; Ye et al, 2019 ; Wang et al, 2021 ); one Wu Qin Xi Qigong (Xiao et al, 2020 ); one Korean qigong (Yang et al, 2005 ); and two just mentioned qigong (von Trott et al, 2009 ; Teut et al, 2016 )]. There were five control comparators included nonphysical therapy [usual care (Cheung et al, 2014 ; Ding, 2014 ; Teut et al, 2016 ; Qiu, 2018 ; Ye et al, 2019 ); wait list (Raub, 2002 ; Yang et al, 2005 ; von Trott et al, 2009 ); education (Cheung et al, 2017 ; Hu, 2017 ); attention control group (Song et al, 2017 )], physical therapy (Wang et al, 2016 ; You et al, 2018 ; Xiao et al, 2020 ), quadriceps strengthening exercises (QSEs) (Wang et al, 2021 ), core stabilization (Liu et al, 2019 ), and stretching (Cao, 2018 ). The intervention duration of all mindful exercises was between 4 and 24 weeks, and sessions ranged from 8 to 96 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations